Perilaku Kecanduan Judi Online Pada Sebagian Kalangan Mahasiswa - Ahmad Nazarudin Ariyanto; Ahmad Assrofun Niam; Rauly Sijabat (JURNAL ILMIAH NUSANTARA, 2026)
The rapid development of digital technology has increased students’ access to online gambling, which may lead to addictive behavior. This study aims to explore and describe online gambling addiction among university students and the factors underlying this behavior. A qualitative descriptive approach was employed, with data collected through in-depth interviews, observation, and documentation involving students who remain actively engaged in online gambling at a university environment in Semarang City. Data were analyzed through data reduction, data display, and conclusion drawing. The findings indicate that online gambling addiction is characterized by a loss of self-control, high intensity of gambling activity, and repeated failure to stop despite awareness of its negative consequences. Initial involvement is influenced by the social environment and early winning experiences, while the continuation of gambling behavior is reinforced by emotional drives and the desire to recover losses. This behavior negatively affects students’ financial, academic, and psychological conditions and has the potential to reduce the quality of students as future human resources.